British industrial investment in Malaysia, 1963-1971 - Junid, Saham (Oxford University Press, 1980)
The development of the Malaysian economy currently inherited from the previous three levels, beginning with the level of growth and rapid development of the natural resources industry, especially tin and rubber starting from the mid 19th century until the year 1914, followed by a period of volatility or instability of the natural resources industry in the period between the First and Second World War and last but not least the level of consolidation and rationalisation of the natural resources industry together with a diversified economy after 1945.[1] For the purposes of smoothness and consistency in understanding the history of foreign investment during the British colonial and Malaysian post colonial periods, the history of foreign investment in Malaya[2] will be analyzed in advance. The background of the study will focus on Malaya since the formation of its economy is the cord to the formation of the Malaysian economy. However, the contribution of Sabah dan Sarawak economic development in the formation of Malaysia's economy could not be denied.